2016
DOI: 10.1093/jac/dkw496
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of cefazolin before, during and after cardiopulmonary bypass to optimize dosing regimens for children undergoing cardiac surgery

Abstract: We propose an optimized dosing regimen for cefazolin during cardiac surgery in paediatric patients to avoid treatment failure due to inadequate antibiotic prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 46 publications
3
28
1
Order By: Relevance
“… who found a fluctuation of CXM protein binding less than 2% during adult cardiac surgery. Even the variation of the highly protein‐bound antibiotic cefazolin with a subsequently higher susceptibility to changes in plasma proteins was minimal (28% ± 3%) in a group of children similar to ours using a reconstituted blood prime on CPB , with a negligible effect of varying albumin concentrations on PTA .…”
Section: Discussionsupporting
confidence: 68%
“… who found a fluctuation of CXM protein binding less than 2% during adult cardiac surgery. Even the variation of the highly protein‐bound antibiotic cefazolin with a subsequently higher susceptibility to changes in plasma proteins was minimal (28% ± 3%) in a group of children similar to ours using a reconstituted blood prime on CPB , with a negligible effect of varying albumin concentrations on PTA .…”
Section: Discussionsupporting
confidence: 68%
“…This may also affect the cefazolin plasma concentration and account for the more profound decrease in the larger CPB system. Recently, De Cock et al published in vivo data on cefazolin plasma concentration during and after pediatric cardiac surgery . The authors collected blood samples from children undergoing cardiac surgery and concentration‐time profiles were analyzed using population pharmacokinetic modeling .…”
Section: Discussionmentioning
confidence: 99%
“…To date, no uniform guidelines for the dosing of antibiotic prophylaxis in children are available. Also, potentially increased risks of SSI after cardiac surgery are not incorporated in current dosing advice . Several procedural risk factors, such as the use of a bladder catheter, longer duration of CPB or prolonged surgery time, may increase the risk of SSI in pediatric cardiac surgery patients .…”
Section: Discussionmentioning
confidence: 99%
“…Caffarellie et al also reported that the traditional dosing protocol of cefazolin was unable to maintain drug concentrations above 8 μg mL −1 in 50% of the patients when surgical time was longer than 120 minutes. De Cock et al performed population pharmacokinetic analysis on total and unbound plasma cefazolin concentrations in 54 children undergoing cardiac surgery with CPB. They concluded that an additional bolus dose at the start of CPB may improve the probability of target attainment from 59% to >94% in a typical pediatric patient.…”
Section: Discussionmentioning
confidence: 99%
“…To establish an effective antimicrobial prophylaxis regimen with cefazolin for patients undergoing cardiothoracic surgery with CPB, we should develop a pharmacokinetic model that describes the disposition of plasma unbound drug during operation. The pharmacokinetics of plasma unbound cefazolin during CPB may be influenced by complex physiological changes associated with the procedure (including low serum albumin levels, transient increase in volume of distribution by connecting the CPB circuit to systemic circulation, changes in circulating volume by infusion and blood loss, and changes in liver and kidney perfusion) . The disposition of cefazolin may be particularly susceptible to alteration associated with CPB‐induced physiological changes, since the drug has a small volume of distribution (0.19 L kg −1 or 11.4 L per 60 kg) and binds extensively to albumin (80%‐86%) .…”
Section: Discussionmentioning
confidence: 99%